2018
DOI: 10.1136/annrheumdis-2018-213028
|View full text |Cite
|
Sign up to set email alerts
|

Increased autophagy is cytoprotective against podocyte injury induced by antibody and interferon-α in lupus nephritis

Abstract: Podocyte autophagy is activated in lupus-prone mice and patients with lupus nephritis. Increased autophagy is cytoprotective against antibody and interferon-α induced podocyte injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 64 publications
4
67
0
Order By: Relevance
“…Intensification of autophagy in podocytes might originate from stress in the glomerulus caused by deposited immune complexes or local inflammatory cytokines and activating autophagy via ROS production or mTORC1 inhibition . Notably, autophagy inhibition aggravated podocyte damage whereas its inducer relieved the injury . This reinforces the notion that both aberrant systemic immunity and intrarenal immunopathology contribute to lupus nephritis, in which autophagy may exert an important effect.…”
Section: Renal Impairmentsupporting
confidence: 63%
See 3 more Smart Citations
“…Intensification of autophagy in podocytes might originate from stress in the glomerulus caused by deposited immune complexes or local inflammatory cytokines and activating autophagy via ROS production or mTORC1 inhibition . Notably, autophagy inhibition aggravated podocyte damage whereas its inducer relieved the injury . This reinforces the notion that both aberrant systemic immunity and intrarenal immunopathology contribute to lupus nephritis, in which autophagy may exert an important effect.…”
Section: Renal Impairmentsupporting
confidence: 63%
“…Future comprehensive studies are needed in renal cell cultures, human kidney tissues, and experimental animal models to elucidate the role of renal resident cells autophagy in the pathogenesis of lupus nephritis (LN). Our recent data indicated that autophagy was increased in kidney tissue from lupus prone MRL lpr/lpr mice with nephritis, compared with MRL lpr/lpr mice without nephritis or C57BL6/J mice [98]. Autophagosomes were observed in podocytes from MRL lpr/lpr mice with nephritis and in human patients with LN.…”
Section: Renal Impairmentmentioning
confidence: 90%
See 2 more Smart Citations
“…In its phosphorylated form, NRBF2 inhibits autophagy, while promoting it in its unphosphorylated form . Intact autophagy, in turn, was recently reported to confer protection against autoimmune disorders such as lupus nephritis . Thus, one could speculate that NRBF2 autoantibodies may have a protective role against damage acquisition by inhibiting NRBF2 phosphorylation and thereby promoting autophagy.…”
Section: Discussionmentioning
confidence: 99%